Sistema de captação de energia solar para uma torre de dessalinização térmica com recuperação de calor - Alves, Régio Davis Barros (2009)
This dissertation presents the experimental result of a system to absorb solar energy to heat up a desalination tower with heat recovery mechanism and a change made in the heated water distribution at the heat storage tank. The system to absorb solar energy consists of solar thermal flat plate collectors for high temperatures and it responsible for the conversion of solar radiation in thermal energy to heat up the water to be desalinated. The change made in the storage tank consists of the installation of a stainless steel pipe with holes equally spaced and arrangement to allow a better distribution of the hot water from the solar collectors in the heat storage tank. The desalination unit has two components: two high temperatures solar collectors and a desalination tower with six stages. In its operation, water is heated in the solar collectors and moves by natural convection to the storage tank, to the bottom of the tower. In the tank, the water transfers heat to the salty water in the first stage of the tower. This heated water transfer heat by evaporation, convection and radiation to the second stage and part of its energy is lost to the ambient. The condensed vapor on the walls of the stages flows down by gravity to be collected in a reservoir installed under the desalination tower. The heat received by the second stage is used to heat up the ater in this stage and the process is repeated in all stages. The performance of the desalination unit was satisfactory. The temperature in the storage tank reached values near 85°C and the water temperatures at the outlet of the solar collector were near 100°C. The daily production was 31 liters of desalinated water and the GOR-value (gain output ratio) was 1,54